Eye Tracking Effort Expenditure and Autonomic Arousal to Social and Circumscribed Interest Stimuli in Autism Spectrum Disorder. - Traynor, J. M.; Gough, A.; Duku, E.; Shore, D. I.; Hall, G. B. C. (Journal of Autism & Developmental Disorders, 2019)
The social communicative deficits and repetitive behaviours seen in Autism Spectrum Disorder (ASD) may be affected by altered stimulus salience and reward attribution. The present study used eye tracking and a behavioural measure to index effort expenditure, arousal, and attention, during viewing of images depicting social scenes and subject-specific circumscribed interests in a group of 10 adults with ASD (mean age 25.4 years) and 19 typically-developing controls (mean age 20.7 years) Split-plot and one-way repeated measures ANOVAs were used to explore results. A significant difference between the ASD and control group was found in the amount of effort expended to view social and circumscribed images. The ASD group also displayed significant differences in pupillary response to social and circumscribed images, indicative of changes in autonomic arousal. Overall, the results support the social motivation hypothesis in ASD (Chevallier et al., Trends Cogn Sci 16(4):231–239, 2012) and suggest a role for autonomic arousal in the ASD symptom dyad.